Diagnosis of the Skills of the Master's Degree: Case Study at the University Pablo of Olavide - Eva Ordóñez Olmedo; Miguel Baldomero Ramírez Fernández (Springer, 2017)
The work team of the Postgraduate Studies Centre (henceforth CEDEP) of Pablo de Olavide University (henceforth UPO) has submitted a questionnaire in order to identify the training needs of the directors of the master's degrees which are implemented in The UPO during the academic year 2016/2017. This article aims to analyze how the lessons are planned and how the acquisition of the competencies defined in each master's degree are achieved, in order to assess the current situation and propose solutions for university quality improvement. This research presents a mixed design: quantitative and qualitative non-experimental descriptive through a questionnaire. Further to the study analysis conducted, the need to create a manual of recommended practice to arrange curricula by competencies at the master level is presented, as 62.16% of the participants reflect a great lack of knowledge about the theoretical description of the competencies classification and 73% support a complementary material need for the design of the curriculum.